PERBANDINGAN PERENCANAAN PORTAL BAJA DENGAN SAP2000 DAN ETABS - Amir Mukhlis (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
This investigation was aim to find the illustration of structural steel design, using SAP2000 software, and to find how far the result different of structural steel by using ETABS. This investigation is background by the difference of design result by using both of the software. Is conducted by making simulation at two application software which used in structural steel design, those are SAP2000 and ETABS. The object were used is plane frame at 7 story steel structure building. The restrain at the structural steel frame is fixed. Both of software is determined by AISC LRFD 93 code. Structure is loaded by distributed load and point load, vertically and horizontally.Shear modulus on both application is cannot determined by the user. The structual design result shows there is no difference significanly for normal force diagram, shear force diagram and moment diagram. The design result shows the difference of structural check. The higher structural check value is 0.972 for SAP2000 and 0.920 for ETABS. Although both of structural check result of the design is different, the structure is still safe or it is not more than 1.00 value.